Actual and Ideal Leadership Behavior Shift within the Last Five Years - YURTKORU, EMİNE SERRA (ELSEVIER SCIENCE BV, 2011)
The main objective of this research is to compare and analyze the shift in the ideal and actual leader behaviors within five years. Therefore two studies were conducted, one during 2004-2005 and the second during 2009-2010 periods. In order to measure the perceived leader behavior and the ideal leader behavior required by the employees, Stogdill's Leadership Behavior Description Questionnaire XII (LBDQ XII) was used. Sample of the Time I Study consisted of 678, and the Time II Study 789 questionnaires. Results revealed that during the last five years there are significant changes in the twelve dimensions of actual and ideal leader behaviors. While the leaders started to perform these behaviors less, the desire to have leaders showing these behaviors also diminished by employees. Even though there is a decrease in the results, when the higher order dimensions - system and person oriented behavior - calculated and compared, we still see that Turkish employees wants both system and person oriented leaders. Only the spread is not as extreme as before. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility 7th International Strategic Management Conference
Keywords: Actual Leadership Behavior; Ideal Leadership Behavior; LBDQ XII; CULTURE; VALUES